The Technoaesthetics of Data Centre “White Space” (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Abstract | Why are the walls, floors, and ceilings of data centres always painted white? Photographs of data centre interiors tend to focus on the advanced technologies contained within them, while the surrounding white surfaces disappear into the background. Bringing this overlooked design feature to the foreground, this essay explores the technical functions, temporalities, and transparencies of white space within data centres.Résumé | Pourquoi les murs, les planchers et les plafonds des centres de données sont-ils toujours peints en blanc? Les photographies de l’intérieur des centres de données ont tendance à se concentrer sur les technologies de pointe qu’elles contiennent, tandis que les surfaces blanches environnantes disparaissent en arrière-plan. En mettant en lumière cet élément de conception souvent négligé, cette étude explore les fonctions techniques, les temporalités et les transparences de l’espace blanc dans les centres de données.